ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN RETRIBUSI PELAYANAN PASAR DI KOTA AMBON - Ekron Rupisiay; Jefry Gaspersz; Paul Usmany; Maryam Sangadji (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the factors that influence the receipt of market service levies in Ambon City. This research is field research or survey with a quantitative approach, so the data used is primary data from questionnaires. The population in this study were Mardika market traders in Ambon City, with a sample size of 90 traders spread across Mardika Market. Hypothesis testing uses Structural Equation Modeling- Partial Least Square (SEM-PLS) with the help of SmartPLS 3.0 software. The results of this research show that market service levy rates, service level quality and knowledge and understanding of levies have a positive and significant effect on market service levy receipts. Intervening testing shows that the willingness to pay levies can mediate market service levy rates, knowledge and understanding of levies on the acceptance of market service levies, while the willingness to pay levies cannot mediate the quality of service levels on the acceptance of market service levies.